PENEGAKAN HUKUM MEREK DALAM HUKUM INDONESIA TERHADAP PEMENUHAN KETENTUAN TRIPS- WTO - Sudjana Sudjana (Fakultas Hukum Universitas Komputer Indonesia, 2021)
Indonesia needs to apply the TRIPs-WTO Agreement in its national law because it has ratified the International Agreement through Law No. 7 of 1994. Therefore, this study raises issues regarding the application of the provisions of the WTO TRIPs Agreement on Trademarks in Indonesian Positive Law, and the Obstacles to the Indonesian Trademark Law in fulfilling the requirements in law enforcement as stipulated in the TRIPs-WTO agreement. The approach method used is juridical normative or doctrinal through a statute approach and a conceptual approach. The research was conducted through literature studies to examine primary legal materials, secondary legal materials, and tertiary legal materials as well as data analysis methods carried out through qualitative normative. The results of the study show that the provisions of the TRIPs-WTO Agreement on Trademarks have been applied in Indonesian Positive Law and even exceed the minimum standards required by the International Agreement. The obstacles to the Indonesian Trademark Law to meet the requirements in law enforcement as stipulated in the TRIPs-WTO Agreement include legal substantiations, legal structures and legal culture of society.